OMERACT GCA phantom project: validation of a 3D-printed ultrasound training phantom for diagnosis of giant cell arteritis - Annamaria Iagnocco; Christian Dejaco; Richard J Wakefield; Stavros Chrysidis; Sara Monti; Thomas Daikeler; Esperanza Naredo; Lene Terslev; Wolfgang A Schmidt; Alojzija Hočevar; Christina Duftner; Chetan Mukhtyar; et al. (RMD Open)
Objective Ultrasonography is crucial for diagnosing giant cell arteritis (GCA); however, training opportunities are rare. This study tested the reliability of ultrasonography findings and measurements of the intima-media thickness (IMT) among ultrasonography experts by using phantoms of the axillary (AA) and temporal arteries (TA) created with high-resolution 3D printing.Methods Twenty-eight participants from 12 European countries received eight sets of phantoms of the AA and the superficial TA (including common, frontal and parietal branches), which were examined in a blinded fashion according to a predefined protocol and evaluated based on Outcome Measures in Rheumatology (OMERACT) GCA ultrasound definitions. Due to difficulties with the delineation of the intima-media complex, the parietal branch of the phantoms was modified, and a second round was conducted. The IMT was measured, and phantoms were classified as normal or vasculitic.Results In both rounds, the phantoms were correctly classified as normal/abnormal in >81% of cases yielding a Fleiss’ kappa of 0.80 (95% CI 0.78 to 0.81) in round 1 and 0.74 (95% CI 0.72 to 0.75) in round 2. IMT measurements revealed an intraclass correlation coefficient (ICC 1.1) of 0.98 (95% CI 0.98 to 0.99) in both rounds. Intrarater reliability was good with a median Cohens Kappa of 0.83 and median ICC of 0.78.Conclusion The study demonstrated high reliability among ultrasound experts in applying the OMERACT ultrasound definitions for GCA and in measuring the IMT using a 3D-printed phantom of the AA and TA. This phantom could assist clinicians in training to assess the large arteries of patients with suspected or established GCA.